Konsep Harmony dalam Perancangan Interior Kantor SAMSAT di Surabaya Barat - Nathania, Stella (Intra, 2013)
Samsat as one of the government offices that are frequently visited by the public has very minimal facilities and making people very uncomfortable and have to use the services of brokers to take care of motor vehicle documents. Although the cost is more, but people do not mind to use the services of brokers. Laying counter irregular and unclear instructions that make the circulation in the office of the financial services sector into chaos. This design is intended to solve the existing problems in the office at the time of the call centers. Authors intended that the public can have the will to take care of themselves letter without having to use the services of brokers. Use the services of brokers is not only detrimental to the public but also detrimental to the government. The concept of harmony is applied here to support SAMSAT office interior design.